The use of post-cycle therapy is associated with reduced withdrawal symptoms from anabolic-androgenic steroid use: a survey of 470 men - Bonnie Grant; Joseph Kean; Naim Vali; John Campbell; Lorraine Maden; Prun Bijral; Waljit S. Dhillo; James McVeigh; Richard Quinton; Channa N. Jayasena (BMC, 2023)
Abstract Background Anabolic-androgenic steroids (AAS) mimic the effects of testosterone and may include testosterone itself; they are used for body enhancement within the general population. AAS use has been linked with increased mortality, cardiovascular disease, mental health disorders, and infertility. AAS-induced hypogonadism can persist for an uncertain time period despite cessation, during which men may report physical and neuropsychiatric symptoms. In an attempt to mitigate these symptoms and expedite testicular recovery, many men self-administer post-cycle-therapy (PCT), typically involving human chorionic gonadotrophin (hCG) and selective oestrogen receptor modulators (SERMs), which are known to potently stimulate testicular function. However, this practice has no objective evidence of effectiveness to lessen the severity or duration of hypogonadal symptoms. Methods An anonymous survey of four-hundred-and-seventy men using AAS explored the symptoms they experienced when ceasing AAS use; the effect of PCT on relieving their symptoms, and their perceived role for health service support. Results The majority of respondents were white, aged 18-30 years old, and working in skilled manual work. 51.7% (n = 243) reported no issues with AAS use, but 35.3% reported increased aggression. 65.1% (n = 306) of respondents had attempted AAS cessation and 95.1% of these experienced at least one symptom upon AAS cessation. Low mood, tiredness and reduced libido were reported in 72.9%, 58.5% and 57.0% of men stopping AAS use, respectively, with only 4.9% reporting no symptoms. PCT had been used by 56.5% of respondents with AAS cessation and mitigated cravings to restart AAS use, withdrawal symptoms and suicidal thoughts by 60%, 60% and 50%, respectively. The effect of stopping AAS on body composition and recovery of testosterone or fertility was a concern in 60.5% and 52.4%, respectively. Most respondents felt PCT should be prescribed under medical supervision in the community. Conclusions Our survey suggests that the majority of men stopping AAS use are using some form of PCT. Some self-reported symptoms of AAS-induced hypogonadism such as cravings to restart AAS use reduce by 60% and suicidal thoughts reduce by 50%. These individuals are concerned about the negative effect of AAS use and cessation. This study provides crucial information for planning future research to evaluate the effects of PCT on symptoms when men stop AAS use.